FUNCTIONAL SIMULATION OF PRODUCTION OF METHYL TERTIARY BUTYL ETHER - R. Yu. Tarasenko; E. V. Burlyaeva (Тонкие химические технологии, 2013)
On the basis of functional modeling methodology a complex of models in IDEF0 notation was created. It describes the production technology and quality control procedure for methyl tertiary butyl ether manufacturing.